1997
DOI: 10.1063/1.473904
|View full text |Cite
|
Sign up to set email alerts
|

Reaction on the O−+CH4 potential energy surface: Dependence on translational and internal energy and on isotopic composition, 93–1313 K

Abstract: Rate constants have been measured for the reactions of O Ϫ with CH 4 , CH 2 D 2 , and CD 4 as a function of ion-neutral average center-of-mass kinetic energy, ͗KE cm ͘, at several temperatures over the range 93 K-565 K using a selected ion flow drift tube apparatus. For the CH 4 reaction we also report measurements made using a high-temperature flowing afterglow ͑HTFA͒ instrument over the temperature range 300 K-1313 K. The rate constants are found to have a very large isotope effect, with the CH 4 rate consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…Firstly, the thermochemistry calculations were carried out for reaction (2) at the second-order Møller-Plesset (MP2) [ 26 , 27 , 28 , 29 , 30 ] perturbation method with 6 − 31 + G(d) basis set. The energetic release Δ E of −0.23 eV is in good agreement with the previous values [ 19 , 20 , 21 , 23 , 24 ], suggesting that the MP2/6 − 31 + G(d) level is reliable in elaborating the reaction process. Excluding the influence of any electrostatic interactions between O − and CH 4 at the initial step in the dynamic simulations, we performed the interaction energy calculations for the three attack modes at the MP2/6 − 31 + G(d) level.…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations
“…Firstly, the thermochemistry calculations were carried out for reaction (2) at the second-order Møller-Plesset (MP2) [ 26 , 27 , 28 , 29 , 30 ] perturbation method with 6 − 31 + G(d) basis set. The energetic release Δ E of −0.23 eV is in good agreement with the previous values [ 19 , 20 , 21 , 23 , 24 ], suggesting that the MP2/6 − 31 + G(d) level is reliable in elaborating the reaction process. Excluding the influence of any electrostatic interactions between O − and CH 4 at the initial step in the dynamic simulations, we performed the interaction energy calculations for the three attack modes at the MP2/6 − 31 + G(d) level.…”
Section: Methodssupporting
confidence: 89%
“…For this reaction mechanism, Comer and Schulz reported an associative-detachment channel [ 18 ], O − + CH 4 → CH 3 OH + e − and it was proved to be an exothermic process (∆ H = −2.43 eV [ 9 ]). In the subsequent experimental studies [ 19 , 20 , 21 , 22 , 23 ], the other reaction pathway [ 19 , 20 , 23 , 24 ], O − + CH 4 → OH − + CH 3 (∆ H = −0.26 eV) was characterized as an exothermic process, in which OH − was formed via direct H-abstraction via the transition-state complex [O-H-CH 3 ] − [ 21 ]. On the basis of the measurements of energy and angular distributions of the product OH − , Carpenter and Farr proposed two mechanisms for the above reaction, namely, one is the collisions of O − with H atom oriented essentially along the relative velocity vector and the other one is the collisions of O − with one of the three off-axis hydrogen atoms [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15,19,20,32,34,35], there is compelling evidence that, if these species are generated, their reactions with hydrocarbons including methane will be facile even under ambient conditions (for an alternative view see, however, [13]f). This has already been demonstrated as early as 1969 by Bohme and Fehsenfeld [41] and later confirmed by Viggiano et al [42], when they reported that atomic [O] •− brings about efficient room-temperature HAT from various alkanes, Eq. (8), in the gas phase.…”
Section: Cleavage Of the C H Bond: The Decisive Step In Heterogeneousmentioning
confidence: 59%